2016
DOI: 10.1186/s12917-016-0842-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of β-caryophyllene to combat bacterial dental plaque formation in dogs

Abstract: BackgroundPeriodontal disease is a highly prevalent illness that affects many dogs, reaching up to 85 % prevalence in individuals over the age of 4 years. Currently the drug of choice for combating the formation of dental plaque in these animals, the etiologic agent of the disease, is chlorhexidine, which has several side effects reported. Thus, surveys are conducted throughout the world in order to identify potential substitutes for antimicrobial therapy and prevention of periodontal disease. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…BCP is a bicyclic sesquiterpene, with a cyclobutane ring, usually found in EOs of oregano, cinnamon, and black pepper (Gertsch et al 2008). Studies have shown that BCP has great potential as an antimicrobial agent in the food industry, due to its low toxicity (Pieri et al 2016). BCP has been known for its anticancer, antioxidant, and anti-inflammatory attributes (Dahham et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCP is a bicyclic sesquiterpene, with a cyclobutane ring, usually found in EOs of oregano, cinnamon, and black pepper (Gertsch et al 2008). Studies have shown that BCP has great potential as an antimicrobial agent in the food industry, due to its low toxicity (Pieri et al 2016). BCP has been known for its anticancer, antioxidant, and anti-inflammatory attributes (Dahham et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…BCP has been known for its anticancer, antioxidant, and anti-inflammatory attributes (Dahham et al 2015). Previously, studies conducted in the plant extracts containing BCP from Lantana sp., Lippia gracillis, Spiranthera odoratissima, Syzygium cumini, Thymus kotschyanus, and Vernonia remotiflo rae V. bra siliana have shown their antimicrobial activity (Pieri et al 2016). However, there has been paucity in information about the mechanisms of the reported antibacterial activity of BCP.…”
Section: Introductionmentioning
confidence: 99%
“…and Lactococcus sp. also appears in the literature . In a study on antibactericidal action of polyunsaturated long‐chain fatty acids (PUFA‐CL) on Propionibacterium acnes and S. aureus, Desbois et al .…”
Section: Discussionmentioning
confidence: 99%
“…also appears in the literature. 57,58 In a study on antibactericidal action of polyunsaturated long-chain fatty acids (PUFA-CL) on Propionibacterium acnes and S. aureus, Desbois et al report that DHA was the PUFA with the highest relative potency against S. aureus and the second most active against P. acnes. 59 In a dose-dependent manner, DHA reduced in vitro growth and in vivo colonization of H. pylori, and contributed to a lower recurrence of infection.…”
Section: Discussionmentioning
confidence: 99%
“…(E)-Caryophyllene is a generally recognized as safe (GRAS) food cannabinoid, and its use is approved by the United States Food and Drug Administration (FDA). Its biological activities are widely reported in the literature, such as those against bacteria, [36], fungi [37], and viruses [38]. There are also reports of its anti-inflammatory [39], anticancer [40], analgesic [41], and antiphytoviral [42] activities.…”
Section: Chemical Composition Of the Eomentioning
confidence: 99%